ALUNOS PRECOCES COM INDICADORES DE ALTAS HABILIDADES/SUPERDOTAÇÃO NA EDUCAÇÃO INFANTIL: INSTRUMENTALIZAÇÃO DOCENTE - MARIANA PATRICIA SOARES DE OLIVEIRA (2022)
The present study has focused on precocity and indicators of giftedness in Early Preschool Education. Individuals with giftedness are considered to be those who present superior potential in one or more areas or branches of knowledge in relation to other who are part of the group in which they are inserted. Although the area of giftedness in Brazil, has been constituted based on studies and research regarding education, there is a subgroup that is part of this branch and has received less attention, called precocious individuals, with reference to children in their first years of life. Precocity is understood as a process that occurs in some children who have a premature development of certain skills, not expected for their age, and can be observed in the family context and also in the school space. Taking into account the existence of mistaken thoughts about individuals with giftedness and, mainly, with those who manifest precocity in Early Preschool Education, as well as the paucity of research and instruments in this area capable of helping the teacher in the identification of precocious children, this study aimed to analyze the adequacy and validity of the "Checklist for identification of precocity and giftedness indicators" for the stage of Early Preschool Education in order to contribute to the construction of an identification instrument. It is characterized as a quantitative-qualitative research, which initially involved the analysis of the Checklist for identifying precocity and giftedness indicators by a Committee of Experts, in order to adapt it to Early Preschool Education, originating the first version of the Precocity Identification Scale and Giftedness Indicators, Early Childhood Education version (EIPIAHS-EI) (Escala de Identificação de Precocidade e Indicadores de Altas habilidades/Superdotação, versão Educação Infantil), with 63 items. This Scale was answered by 128 teachers from public and private schools, from preschool classes situated in some cities of Mato Grosso do Sul. After completing the Scale, by teachers, its items were statistically analyzed through Exploratory Factor Analysis, with support of the statistical software Statistical Package for the Social Sciences (SPSS), in order to analyze its dimensionality. We came to a new configuration of the EIPIAHS-EI with 14 items divided into three dimensions: “Learning and treatment of information”, “Motivation and genuine interest” and “Aspects with a tendency to negative interpretation”. It is expected that the Scale might be an instrument capable of helping the teacher to recognize and signal early learners with giftedness indicators in Early Preschool Education, with a view to offer, as soon as possible, an education that considers their learning particularities, rescuing these individuals from invisibility.